Factors Inhibiting the Application of SAK-EMKM in Financial Report on MSMEs - Kartikasari, Evi Dwi; Yanto, Yanto; Rodhiyah, Ma’rufatur; Dedyansyah, Achmad Farid; Binti Zainuddin, Siti Afiqah (Universitas Prasetiya Mulya, 2024)
The existence of MSMEs can be believed to reduce unemployment and crime rates in the community so MSME empowerment needs to be improved properly. Most of the residents of Sambeng Village are MSME actors, but in their MSME activities, only 3.02% have business licenses. Policies related to obtaining capital with government facilities, namely low-interest credit, require financial reports that comply with the SAK-EMKM standards. This study aims to explore more deeply the implementation of SAK-EMKM in MSME financial reports. The method is descriptive qualitative with primary data sources. A sample of 95 based on purposive sampling. The results of the study showed that many MSMEs in Sambeng District have not implemented financial reports by SAK-EMKM, namely 73% of 95 respondents. Factors that hinder MSME actors from implementing EMKM-SAK are education, literacy, and capital sources. Based on the questionnaire, MSME actors whose capital sources are loans from banks that implement EMKM-SAK and for their capital, on average do not implement.